Fabrication and characterization of electrospun poly-DL-lactide (PDLLA) fibrous coatings on 45S5 Bioglass® substrates for bone tissue engineering applications - Yunos, D. M.; Ahmad, Z.; Boccaccini, Aldo R. (Journal of Chemical Technology and Biotechnology, 2010)
BACKGROUND: This work focuses on combining electrospun biodegradable poly-DL-lactide (PDLLA) fibres and 45S5 Bioglass® for tissue engineering applications. RESULTS: A variety of fibrous structures were produced upon application of an electric field to a flowing solution of PDLLA (5 wt/v%) in di-methyl carbonate (DMC). Electrospinning was achieved at an applied voltage of 8.5 kV for a fixed flow rate of 5 μ Lmin-1. Scanning electron microscopy images of PDLLA fibres deposited on 45S5 Bioglass® sintered pellets revealed that the fibres had diameters in the range 100-200 nm, leading to increased surface roughness, as assessed by white light interferometry. Bioactivity studies on PDLLA fibre coated Bioglass® substrates were carried out in simulated body fluid (SBF) for 7, 14 and 28 days. It was found that mineralization of PDLLA fibres on 45S5 Bioglass® substrate (formation of hydroxyapatite) occurred after 7 days of immersion in SBF and full coverage of PDLLA fibres with HA nanocrystals was achieved after 14 days in SBF. CONCLUSION: The approach investigated represents a convenient method to develop a controlled mineralized fibrous topography on bioactive glass substrates for improved cell attachment, which can be exploited in bone tissue engineering applications. ©2009 Society of Chemical Industry.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.fabric_8
Keywords: Bioactive glass substrates; Bioactivity studies; Electrospinning; Light interferometry; PDLLA fibres; SBF; Tissue engineering